1994
DOI: 10.1002/ar.1092400415
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localization of the high‐affinity NGF receptor (gp 140‐trkA) in the adult human dorsal root and sympathetic ganglia and in the nerves and sensory corpuscles supplying digital skin

Abstract: Present results provide evidence for the localization of gp140-trkA-like IR in: (1) nerve cells which are known to be NGF-responsive, and (2) non-nervous cutaneous tissues which are innervated by NGF-dependent peripheral neurons. These findings suggest that, in addition to the well-established role of NGF on sensory and sympathetic neurons, this neurotrophin may be able to regulate some other functions on non-nervous cells which are targets for NGF-dependent peripheral neurons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1
2

Year Published

1996
1996
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 57 publications
2
27
1
2
Order By: Relevance
“…TrkA-like IR was also reported in human cuatenous Meissner and Pacinian corpuscles (Vega et al, 1994b). Furthermore, both p75 (Chesa et al, 1988;Wyatt et al, 1990;Narisawa et al, 1992;Vega et al, 1992Vega et al, , 1993English et al, 1994) and TrkA (Vega et al, 1994b;Shibayama and Koizumi, 1996) are expressed too in different cutaneous nonnervous tissues.…”
Section: Nerves and Sensory Corpusclesmentioning
confidence: 85%
“…TrkA-like IR was also reported in human cuatenous Meissner and Pacinian corpuscles (Vega et al, 1994b). Furthermore, both p75 (Chesa et al, 1988;Wyatt et al, 1990;Narisawa et al, 1992;Vega et al, 1992Vega et al, , 1993English et al, 1994) and TrkA (Vega et al, 1994b;Shibayama and Koizumi, 1996) are expressed too in different cutaneous nonnervous tissues.…”
Section: Nerves and Sensory Corpusclesmentioning
confidence: 85%
“…Vega et al [37] previously reported the occurrence of TrkA immunoreactivity in perineurial cells, endoneurial fibroblasts, Schwann cells and large axons of the nerve truncus supplying human digital skin. In the present study, using the same commercial antibody as that used by the previous authors, we have demonstrated the presence of TrkA immunoreactivity in perineurial cells and axons of the carotid body.…”
Section: Discussionmentioning
confidence: 98%
“…They were then incubated with a rabbit anti-TrkA antibody (Santa Cruz Biotechnology, Inc., Santa Cruz, CA) at 1 mg/ml overnight at room temperature. The specificity of this antibody was characterized in a previous study [37]. After washing with PBS, the immunoreaction sites were made visible by incubating the sections successively at room temperature with a biotinylated anti-rabbit IgG antibody (Vector Laboratories, Inc., Burlingame, CA) diluted at 1:200 in PBS for 1 hr, streptavidin-conjugated horseradish peroxidase (Dakopatts) diluted at 1:500 in PBS for 1 hr, and finally with a mixture of 0.01% 3'-diaminobenzidine tetrahydrochloride and 0.02% hydrogen peroxide in 50 mM Tris-HCl buffer, pH 7.6 [2].…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…In the skin, NTRK1 is expressed in specialized sensory cells (Meissner corpuscles, Pacinian corpuscles, and Merkel-neurite mechanoreceptors). 9 Innervation and development of Merkel cells has been shown to be dependent on NTRK1. 10 Thus, NTRK1 is apparently responsible for normal development of several aspects of peripheral pain sensation.…”
Section: Discussionmentioning
confidence: 99%